Optical properties of artificial intraocular lenses and considerations for additive manufacturing - Brighesh, Bushra; Alsuliman, Noran; Nimer, Ahed; Albosaad, Omnyah; Alokosh, Batool; Alnaili, Tala; Syed, Abeer; Gardner, Michael R. (Frontiers in Medicine, 2025)
Cataracts, a leading cause of blindness in the world, are commonly treated by replacing the ocular lens with an artificial intraocular lens (IOL). The material and structure of the IOL are major factors in their efficacy, affecting, among other characteristics, the optics of the eye. In the recent research record, two optical properties have emerged as standardized characterization methods for IOL optics: (1) optical transmittance and (2) optical scattering. This mini review describes these two methods and collates data in such a way that comparisons may be drawn across four different IOL material types (PMMA, hydrophobic acrylic, hydrophilic acrylic, and silicone) and three IOL conditions (in-vivo, cadaver explant, and inventory control). Finally, the emerging field of additive manufacturing for IOL production is considered. Such technologies hold promise for optimizing IOLs for cataract patients. Researchers in additive manufacturing for IOL production may incorporate optical transmittance and optical scattering as standard characterization methods for 3D-printed IOLs developed by the broader IOL researcher community.